Program Peningkatan Kesejahteraan Kapasitas Keluarga - Monika, Andini; Sudadio, Sudadio; Suherman, Suherman (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
This study aims to determine the effectiveness of family capacity building programs in improving family welfare in Sawah Luhur, Sub-District Kasemen Serang, City Banten Province. This research uses a descriptive method with a qualitative approach, where data obtained from interviews, the source of research data are the coordinator, a companion and 21 participants. The results showed that the effectiveness of the program to increase family capacity in improving family welfare in the Sawah Luhur Village, Kasemen District, Serang City, Banten Province was quite effective, with not many obstacles passed during the program, this was based on information from relevant parties. The results of the program to increase family capacity in improving family welfare have been achieved participants have increased in terms of knowledge, attitudes and independent life skills. Supporting and inhibiting factors in the program held include the level of attendance of learning residents less than the maximum of the organizers there are shortcomings with limitations in the provision of learning media.